1995
DOI: 10.1073/pnas.92.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid development in mice with a targeted deletion of the interleukin 2 receptor gamma chain.

Abstract: The interleukin 2 receptor y chain (IL-2R'y) is a component of the receptors for IL-2, IL-4, IL-7, and IL-15. Mutations in IL-2Ry in man appear responsible for the X chromosome-linked immunodeficiency SCIDX1, characterized by a defect in T-cell and natural killer (NK)-cell differentiation with the presence of poorly functioning B cells. To explore at which level IL-2Ry affects lymphoid development in vivo, we have analyzed mice derived from embryonic stem (ES) cells with mutant IL-2Ry loci generated by Cre/lox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
492
2
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 807 publications
(527 citation statements)
references
References 26 publications
28
492
2
5
Order By: Relevance
“…Consistent with the results obtained from CR␥ Ϫ/Y (31, 32) and CR␥ null mutant (28,29) mice, PP and peripheral lymph nodes, except markedly atrophied MLN, were not detectable in athymic CR␥ Ϫ/Y mice at necropsy. We also examined MLN cells and spleen cells isolated from athymic CR␥ Ϫ/Y mice and found that a TCR Ϫ lymphocyte population that expressed c-kit, Thy-1, CD4, and CD8␣␤ molecules was present exclusively in the IEL compartment (Fig.…”
Section: Distinctive Tcr ϫ Iel Are Localized In the Intestinal Epithesupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with the results obtained from CR␥ Ϫ/Y (31, 32) and CR␥ null mutant (28,29) mice, PP and peripheral lymph nodes, except markedly atrophied MLN, were not detectable in athymic CR␥ Ϫ/Y mice at necropsy. We also examined MLN cells and spleen cells isolated from athymic CR␥ Ϫ/Y mice and found that a TCR Ϫ lymphocyte population that expressed c-kit, Thy-1, CD4, and CD8␣␤ molecules was present exclusively in the IEL compartment (Fig.…”
Section: Distinctive Tcr ϫ Iel Are Localized In the Intestinal Epithesupporting
confidence: 79%
“…1A). Severely diminished development of IEL in CR␥ mutant mice has also been reported (28,29). Surprisingly, we found that lymphoid cell aggregates filled with a meaningful number of c-kit ϩ cells, namely CP, were hardly detectable in the intestinal LP of CR␥ Ϫ/Y mice and that most c-kit ϩ cells were localized individually throughout the length of the small intestine, although two to three c-kit ϩ cells settled together in several locations (Fig.…”
Section: Cr␥ ϫ/Y Mice Lack Cp ␥␦-Iel Cd8␣␣ ϩ ␣␤-Iel and Thy-1 ϫ ␣␤mentioning
confidence: 55%
See 1 more Smart Citation
“…Several signals have been implicated in controlling thymopoiesis including those emanating from the TCR following interactions with self-peptide1MHC (pMHC) and those induced by growth factors including cytokines [12]. Mice lacking the common cytokine receptor gamma chain (g c ) family of cytokines (which comprise IL-2, IL-4, IL-7, IL-9, IL-15 and IL-21) have hypoplastic thymi and a reduced number of T cells, although the T cells generated were able to respond to a range of mitogens [33,34]. Humans possessing mutations in genes encoding the g c , Jak3 (both critical for signal transduction following binding g c cytokines) or the a chain of the IL-7 receptor (IL-7Ra), also display a severe block in T-cell development and resulting severe combined immunodeficiency [35].…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c +/+ weights at weeks [10][11][12][13][14][15][16], that were statistically less than agematched weights of Rag2 −/− /Il2rg −/− , are measurements on animals in our care. At 10 weeks of age, female Rag2 −/− /Il2rg −/− mice were on average 3.2 g heavier that BALB/c mice (P<0.001), a finding that had implications for our anaesthetic protocol and overall postsurgical success for surgical implantation of radiotransmitters in BALB/c control mice (see below).…”
Section: Assessment Of Post-natal Growth Between Mice Gestated In Impmentioning
confidence: 97%